Alrai Media Group - Al-Kanderi, Dalal Qassim (AIBPM Publisher, 2019)
Alrai Media Group is a Kuwait based public shareholding company and is engaged in the media sector. It was established in 2002 December and listed in Boursa Kuwait since 2010 October. The company segregate into two primary sector one is print media segmentation, and another is a publication, distribution in Arabic languages by daily newspapers and audio-video segmentation. It also invites surplus fund in portfolio managers. Alrai Media Group also own the Tv, were this is the first , independent and private Tv sector in the country and international level. The company covers the Gulf region, South Europe, South Asia and North Africa. It represents modern and high professional statin it also focusing on traditions and integrity. Alrai Group great website that has received Sheikh Salem Al Ali award in 2008 this is the best News Website in Kuwait City. The Alrai company operate wholly owned subsidiaries regarding Al Rai Company, Publisher Printing Press Company WLL and Al Rai United Publications Company WLL finally Rai production WLL. Alrai company stock market is Kuwait Stock Exchanges; the official sector is consumer services, market capitalisation size is to be small, paid-up capital 23,303,860 KWD and value per share 100 KWD